Smartphone addiction habit is positively associated with coronary artery disease and its severity in Chinese adults: a case-control study - Zhu, Jun; Wang, Sibo; Wu, Yujie; Gu, Lingfeng; Ma, Yao; Wang, Yaxin; Wang, Liansheng (Frontiers in Cardiovascular Medicine, 2024)
Background: Coronary artery disease (CAD) has a high incidence and poor prognosis worldwide. It has been confirmed that smartphone addiction (SA) habit can increase the incidence of hypertension and obesity in adolescents. However, the association of SA with CAD and its severity in Chinese adults remains largely unknown.Methods: A total of 700 Chinese adults (aged 18-70 years) including 350 CAD patients and 350 control subjects were enrolled. The Smartphone Addiction Scale Short Version (SAS-SV) was used to measure SA habit, and the Pittsburgh sleep quality index (PSQI) was used to assess sleep quality.Multiple logistic regression was employed to analyze the relationship between SA habit and CAD.Results: After adjusting for age, smoking, hypertension, T2DM, and other risk factors, there was a significant association between SA habit and CAD in adults (p < 0.001). Subgroup analysis showed that there were statistical differences in the correlation between SA habit and CAD in the hypertension, ≤55 years age old, and female subgroups. Moreover, we performed a subgroup analysis based on the number of coronary artery lesions. The result showed that the rate of SA habit in the three-vessel disease group was the highest (p < 0.001). We applied Gensini score to evaluate the severity of coronary artery lesions (median Gensini score, 34) and divided all CAD patients into high Gensini score group (>34) and low Gensini score group (≤34), respectively. Compared with low Gensini score group, patients in high Gensini score group were more likely to have SA habit (p = 0.049).Conclusions: There is a positive association of SA habit with CAD and its severity in Chinese adults.